IMPLEMENTASI PROJECT BASED LEARNING PADA MATERI KEANEKARAGAMAN HAYATI DALAM MEWUJUDKAN PROFIL PELAJAR PANCASILA - Idah Hamidah; Atit Suhati; Sugianto Sugianto (Jurnal TPACK IPA, 2025)
The Pancasila student profile is one of the efforts to improve the quality of education in Indonesia that prioritizes character building. However, this has not been optimally realized. This study aims to describe the implementation of project-based learning in realizing the profile of Pancasila students in biodiversity materials. This study uses a descriptive type of research using quantitative research methods. The population in this study is class X7 SMAN 1 Jatibarang with a total of 28 students. The instrument used is for the element of critical thinking using 5 questions in the form of an essay test to measure students' critical thinking ability with the criteria of C3-C5 questions. And to find out the results of student independence, namely using questionnaires and observer assessments. As well as to find out the creativity of students using the assessment of the product produced, namely in the form of posters in accordance with the assessment that has been determined. Based on the results of research and data analysis using the PJBL model to realize several elements in the Pancasila student profile, namely critical reasoning, independence, and creativity, it can be concluded that students' critical thinking skills are obtained from the average data of the critical thinking ability of all students, which is 79% in the good category, and the results of the independence questionnaire obtained 84% data with the very good category. The results of the independence observer assessment obtained 88% data and the last result of the product assessment to measure student creativity was 89% with the good category. Keywords: Pancasila Student Profile, Creativity, Learning Model, PJBL, Biodiversity